Evaluasi Kebijakan Bupati tentang Salat Jamaah di Kabupaten Ogan Komering Ilir, Sumatera Selatan - Kharisma Purwandani; Ridho Al-Hamdi; Dimas Subekti (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2022)
This research focused on evaluation of regent’s circular letter number 352-year 2017 concerning appeal to do fardhu congregational prayer for state civil administration in Ogan Komering Ilir regency and to find out the factors that have led to the success and failure of the regulation. This research method is qualitative using a case study approach. OKI District was chosen as a case because there were still problems with the implementation of the congregational prayer policy for state civil servants. Data collection techniques in this study were interviews and documentation. The result of the study shows that of six indicators, four indicators were successful and two indicators were unsuccessful. The unsuccessful indicators were effectiveness, efficiency, responsiveness, and accuracy, and the successful indicators were adequacy and equality. The successful of adequacy indicators were proven by many mosque facilities that can be used to do congregational prayer in OKI regency. The three factors that influenced successful and unsuccessful of evaluation of this regulation were effectiveness, adequacy, and equality. The factors that influenced the successful of the regulation’s evaluation were adequacy and equality, while the factor influenced unsuccessful of the regulation’s evaluation was effectiveness. The unsuccessful effectiveness indicator is caused by congregational prayer of state civil administration was not working properly. This confirms that the evaluation of this regulation can be concluded unsuccessful, so it is necessary to make some serious effort to improve supervision over the implementation of the regulation.